Dynamic resource scheduling schemes for W-CDMA systems. - Gurbuz, O.
W-CDMA is the strongest candidate for the air interface technology of third-generation wireless communication systems. Dynamic resource scheduling is proposed as a framework that will provide QoS provisioning for multimedia traffic in W-CDMA systems. The DRS framework monitors the traffic variations and adjusts the transmission powers of users in an optimal manner to accommodate different service classes efficiently. Variable and optimal power allocation is suggested to provision error requirements and maximize capacity, while prioritized queuing is introduced to provision delay bounds. A family of DRS algorithms has been devised along these dimensions for obtaining different levels of QoS. The DRS schemes are discussed in terms of queuing and bandwidth allocation with an emphasis on their impact on delay QoS
Keywords: DRS algorithms; DRS framework; QoS provisioning; W-CDMA systems; Air interface technology; Bandwidth allocation; Delay bounds; Dynamic resource scheduling schemes; Error requirements; Maximize capacity; Multimedia traffic; Optimal power allocation; Prioritized queuing; Service classes; Third-generation wireless communication systems; Traffic variations; Transmission powers; Variable power allocation